Towards a common vision of the Church? The Church in the Catholic-Lutheran dialogue - González Montes, Adolfo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
To analyze the situation of the current Catholic-Lutheran dialogue, Malta’sreport, The Gospel and the Church (1972), is taken as a basis, in its first, thirdand fourth points. Thus, we review the diverse understanding of: (1) the primacyof the word of God, with its consequences on Tradition and the Magisterium; (2)the ecclesiastical ministry and its constitutive character for the configuration ofthe Church; and (3) the apostolicity of the Church and its unity. The ecumenicaldocuments after 1972 are brought up to evaluate both the progress made towardsa convergence, and to verify the areas of significant dissent that still continue toseparate Catholics and Lutherans from the desired unity.
Keywords: Scripture; tradition; magisterium; ecclesiastical ministry; apostolicity; sacramentality of the Church; ecclesial unity